2012
DOI: 10.1186/1471-2431-12-23
|View full text |Cite
|
Sign up to set email alerts
|

Weight status and gender-related differences in motor skills and in child care - based physical activity in young children

Abstract: BackgroundOver the last decades, a decline in motor skills and in physical activity and an increase in obesity has been observed in children. However, there is a lack of data in young children. We tested if differences in motor skills and in physical activity according to weight or gender were already present in 2- to 4-year-old children.MethodsFifty-eight child care centers in the French part of Switzerland were randomly selected for the Youp'là bouge study. Motor skills were assessed by an obstacle course in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
1
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 41 publications
2
28
1
1
Order By: Relevance
“…There is a whole body of evidence that studied the association between FMS and body weight and BMI, and most studies suggest a negative association [13,23,24,25]. Although our results confirm these previous data, suggesting a negative association between FMS and body weight and BMI, our study adds to the whole body of evidence by documenting this association with other health indicators and by comparing two fundamental movement skills tools often used in Canada.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…There is a whole body of evidence that studied the association between FMS and body weight and BMI, and most studies suggest a negative association [13,23,24,25]. Although our results confirm these previous data, suggesting a negative association between FMS and body weight and BMI, our study adds to the whole body of evidence by documenting this association with other health indicators and by comparing two fundamental movement skills tools often used in Canada.…”
Section: Discussionsupporting
confidence: 81%
“…In addition, poor FMS was negatively associated with obesity status in children aged between four and six [11]. and even younger (e.g., aged between 2 and 4) [13]. However, in terms of health indicators other than those related to body weight, not much information is available, and tools to assess FMS have not been standardized.…”
Section: Introductionmentioning
confidence: 99%
“…24 Contrary to the above findings, a few studies found no association between weight/BMI on performance tests of manual dexterity and finger tapping. 21,22,62 …”
Section: Resultsmentioning
confidence: 99%
“…The Youp’là Bouge study (clinicatrials.gov NCT00967460) is also a multicenter cluster-randomized physical activity intervention trial in childcare centers performed between 2009 and 2010 [17]. The study randomly selected 58 child care centers from the French part of Switzerland.…”
Section: Methodsmentioning
confidence: 99%